Route des hommes : soixante bois gravés - Masereel, Frans (Zürich : Limmat-Verlag, 1964)
Bibliotheek Camille Huysmans
Dedicator: Masereel, Frans, dedicatee: Rumpel, Heinrich, dedicatee: Huysmans, Camille
Frans
Album
Keywords: Masereel, Frans; grafische kunsten